A scoping review of the working alliance in acquired brain injury rehabilitation. Issue 4 (13th February 2019) - Stagg, Kellie; Douglas, Jacinta; Iacono, Teresa
Abstract: Purpose: The aim was to review the empirical literature to determine the nature and breadth of research into the working alliance in acquired brain injury (ABI) rehabilitation. Methods: A scoping review was conducted, beginning with a systematic search of relevant databases using key search terms. Studies with a focus on the role of the working alliance in shaping rehabilitation outcomes, and factors influencing perceptions of the working alliance were included and key information extracted. Results: A total of 10 quantitative studies met inclusion criteria. In most studies, ratings of the working alliance were compared with other process variables or outcome measures. The working alliance was linked to positive activity and participation outcomes, including return to work, school, and driving. Client related factors such as age, level of education and approach to rehabilitation tasks were associated with client and therapist perceptions of the working alliance. Conclusions: The working alliance emerged as a complex process that interacts with many factors and processes at play in the rehabilitation environment. Notwithstanding the limitations of the research base, findings indicate that enhancement of the working alliance may indeed influence rehabilitation outcomes. Allowing time for the development of the working alliance, and consideration of factors such as therapist skill, may support therapists to strengthen their alliances in ABI rehabilitation. Implications for Rehabilitation: Allowing time for the development of the working alliance has the potential to enhance the alliance and thereby influence rehabilitation outcomes. Factors such as the client's age and level of education may influence the strength of the working alliance, and hence, awareness of these factors may assist clinicians in maintaining strong alliances with all clients. A strong working alliance is possible in the presence of client cognitive impairment, however, the skill of the therapist may be important in managing the potential impact of cognitive impairment on the working alliance.